Predicting the Likelihood of Nonsentinel Lymph Node Metastases in Triple Negative Breast Cancer Patients With a Positive Sentinel Lymph Node: Turkish Federation of Breast Disease Associations Protocol MF09-01 - GÜLLÜOĞLU, MAHMUT BAHADIR (CIG MEDIA GROUP, LP, 2012)
Our aim was to determine the frequency of nonsentinel lymph node involvement of patients with operable triple negative breast cancer and with a positive sentinel lymph node, and to predict the likelihood of nonsentinel lymph node metastases in this cohort of patients by using 4 different nomograms. The accuracy of nomograms in patients for triple negative is yet to be determined. Background: Triple negative (TN) tumor has a relatively high rate of recurrence and distant metastasis, but results of studies revealed that triple positive tumor is an independent predictor of axillary lymph node involvement. Our aim was to evaluate the frequency of nonsentinel lymph node metastasis (NSLNM) involvement in operable TN breast cancer with positive sentinel lymph node (SLN) and predicting the likelihood of NSLNM in this cohort of patients by using 4 different nomograms. Methods: A total of 128 patients with TN and SLN+ underwent complete axillary lymph node dissection in 14 different centers in Turkey. For comparison, we used our previous multicenter MF08-01 Protocol, which identified 441 patients with estrogen receptor (ER+) who had a positive SLN biopsy and underwent subsequent complete axillary lymph node dissection. Turkish, Cambridge, and Stanford nomograms and the Tenon Score system were used to calculate the probability of NSLNM. Results: Patients with TN tumor had a larger tumor size. The actual percentage of NSLN positivity was 41% in the TN group and 47.1% in patient with ER+. The Tenon Score was <= 3.5 in 12% of patients with TN and ER+; the area under the curve in the receiver operating characteristics curve were 0.53 and 0.59, respectively. Based on the Turkish, Cambridge, and Stanford nomograms, areas under the curve were 0.54, 0.53, and 0.61, respectively in patients with TN, and were 0.79, 0.72, and 0.70, respectively, in patients with ER+. Conclusion: Using the Tenon Score system underestimates NSLN positivity, and tested nomograms are not good discriminators of NSLNM in patients with TN and positive SLN. Clinical Breast Cancer, Vol. 12, No. 1, 63-7 (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Breast carcinoma; Nomogram; Nonsentinel lymph node; Sentinel lymph node; Triple negative; HORMONE-RECEPTOR STATUS; GROWTH-FACTOR RECEPTOR; PROGESTERONE-RECEPTOR; TUMOR CHARACTERISTICS; ESTROGEN-RECEPTOR; EXPRESSION; GENE; HER-2/NEU; SURVIVAL; SUBTYPES